The The visual environment as a directorial tool: The art of location in children’s video content - Kozachuk, Volodymyr (Art and Design, 2025)
In the contemporary media landscape, children's video content is one of the leading tools for development, education, and entertainment, while the visual environment acquired the status of an independent language of communication. Despite the widespread presence of children's media products on digital platforms, directorial principles of location design for young audiences remained insufficiently explored in the Ukrainian cultural and artistic context. The study aimed to analyse the role of the visual environment as a directorial tool in the production of children’s video content for digital platforms, using the channels Smile Family and Smile Family Spanish as case studies. The research was based on a review and analysis аof theoretical sources in the fields of perception psychology, colour theory, film language, and semiotics. To examine practical material, methods of visual-structural frame analysis, spatial composition, symbolism, and the organisation of visual elements in locations were applied. The study systematised key directorial techniques for creating visually appealing, emotionally expressive, and narratively coherent environments for child audiences. The research identified typical models for using colour as an emotional and narrative device, principles of symmetrical and asymmetrical composition, techniques for filling space with symbolically charged objects, and the role of editing dynamics in shaping perception. Successful case studies illustrated how a thoughtfully designed location functioned not as a background but as an active participant in the interaction, influencing the rhythm, emotional tone, and narrative structure. The applied methods – analysis of sources in perception psychology, colour theory, and semiotics, along with visual-structural frame analysis – integrated both academic approaches and practical tools for directors and producers. The results contributed to the advancement of directing methods, artistic design, and visual planning in the creation of children’s media content for digital platforms.